An observational study of peripheral intravenous and intraosseous device insertion reported in the United States of America National Emergency Medical Services Information System in 2016. (December 2022) - Mason, Matt; Wallis, Marianne; Barr, Nigel; Bernard, Anne; Lord, Bill
Abstract: Objective: To investigate the prevalence of intravenous and interosseous device insertion in the prehospital setting by prehospital clinicians, and the characteristics of patients receiving these devices as reported to the United States of America National Emergency Medical Services Information System. Methods: A retrospective analysis of the United States of America National Emergency Medical Services Information System public release dataset for the 2016 calendar year. Results: A total of 20, 454, 975 events involving 40, 438, 959 procedures were analysed. One or more peripheral intravenous catheters were inserted during 27.4 % of events, and one or more intraosseous devices in 0.4 % of events. Insertion was completed with one attempt in 71.6 % of peripheral intravenous catheter insertions and 86.9 % of intraosseous devices insertions. Insertion was successful for 74.7 % of peripheral intravenous catheter insertions and 85.4 % of intraosseous device insertions. High rates of peripheral intravenous catheter insertion were found with: being female (51.6 %), aged 40–90 years (80.2 %), having a cardiac rhythm disturbance (70.3 %), having a primary symptom of change in responsiveness (58.7 %), or when there was initiation of chest compressions (50.4 %). There were high rates of intraosseous device insertion if the patient was male (57.8 %), aged 40–90 years (77.2 %), experienced a cardiac arrest (29.2 %), had chest compressions initiated (33.6 %), or died (16.4 %). Scene time was longest for events with intraosseous devices inserted (19.7 min, IQR 13.2–28.6) but transport time shortest (9.0 min, IQR 5.0–15.0). Conclusions: The distribution of patient factors and the insertion of peripheral intravenous catheters and intraosseous devices is described at a national level for the first time. The results provide prehospital clinicians and Emergency Medical Services rigorous data to compare, and possibly improve, practice.